VIEWS AND PERSPECTIVES OF HYPERTENSION EXPERTS IN GREECE REGARDING THE EFFICACY AND SAFETY OR RENAL SYMPATHETIC DENERVATION. (April 2021) - Doumas, Michael; Andreadis, Emmanouil; Davlouros, Periklis; Dimitriadis, Kyriakos; Gkaliagkousi, Eugene; Grassos, Harris; Hatzitolios, Apostolos; Imprialos, Konstantinos; Kalaitzidis, Rigas; Kallistratos, Emmanouil; Konstantinidis, Dimitrios; Kotsis, Vasilios; et al.
Abstract : Objective: The role of renal sympathetic denervation (RSD) in the management of arterial hypertension remains controversial, given the initial enthusiasm by the first studies, the great disappointment by the first sham-controlled randomized study and the current promising finding in recent randomized trials. Therefore, an uncertainty exists about the beliefs of hypertension specialists regarding RSD. This analysis presents the opinions of hypertension experts in Greece regarding the efficacy and safety of RSD. Design and method: Chairpersons of ESH Hypertension Excellence Centers in Greece and their senior clinical research fellows, were invited to participate in a meeting aiming to discuss the current evidence on the clinical utility of RSD. Individual responses were recorded and qualitatively analyzed, in order to reach consensus about the safety and efficacy of RSD. Results: Twenty-five experts participated in the meeting (cardiologists 52%, internists 40%, nephrologists 8%). Participants agreed upon the favorable results of three recent clinical trials and supported the view that RSD is an effective method. 44% believe that further technological development of the denervation catheter is expected to improve the results of the technique. Importantly, 22% of the experts highlighted the additional benefits of the method in regressing target organ damage and in patients with increased activity of the sympathetic nervous system. However, 44% of the experts underlined the lack of reliable predictive markers for the efficacy of RSD, while 32% highlighted the lack of long-term efficacy studies. Experts universally agreed on the safety of the method. However, 64% stated that the duration of the RSD trials was short, and thus there is lack of data on the long-term safety of RDS. Of note, 76% considered the method as easy to perform and minimally invasive. Conclusions: The majority of the hypertension experts in Greece agree upon the efficacy of RSD and all had minimal concerns of the safety of method. More data are needed to reveal the degree of confidence among hypertension experts regarding the efficacy and the safety of the whole procedure and its specific aspects.